Alih Kode dan Campur Kode dalam Pemerolehan Bahasa Anak - Marwan, Iwan (IAIN Kediri, 2016)
This research aims to explains the switch code, structures the code-mixing, and its factor Ã‚Â in child language acquisition. Data source this study is a three-year-old child in a bilingual family. Data collection is carried out by means of observing and reading carefully and repeatedly. Data analysis technique used is descriptive qualitative scientific references with Sociolinguistics (Holmes and Fishman) and language acquisition (Clark & Clark). Based on studies produced two conclusions. First, the switch code and the code mixing in child language acquisition includes verbal, numeral and particles. Second, the structure of the code and code-mixing in language acquisition include sentence structure and sentence statement.Third, some factor in language acquisition are environment, topic, condition and vocabulary limited.Keywords; the switch code and code mixing; form; structure; factor.